The Routine Use of Prophylactic Oxytocin in the Third Stage of Labor to Reduce Maternal Blood Loss. (11th September 2017) - Kuzume, Akiko; Sugimi, So; Suga, Sachie; Yamashita, Hiroshi; Yasuhi, Ichiro
Abstract : Objective . To demonstrate whether or not the routine use of prophylactic oxytocin (RUPO) reduces the blood loss and incidence of postpartum hemorrhaging (PPH). Methods . We used a prospective cohort and a historical control in a tertiary perinatal care center in Japan. In the prospective cohort, we introduced RUPO in April 2012 by infusing 10 units of oxytocin per 500 mL of normal saline into a venous line after anterior shoulder delivery (RUPO group). In the historical control, oxytocin was administered via a case-selective approach (historical control group). We included completed singleton vaginal deliveries and compared the volume of blood loss and the incidence of PPH between the groups. Results . We found a significantly lower volume of blood loss (520 ± 327 versus 641 ± 375 mL, p < 0.001 ) and a lower incidence of PPH (6.1% versus 14.0%, p < 0.001 ) in the RUPO group (n = 392 ) than in the control group (n = 407 ). Although the oxytocin dose was significantly higher in the RUPO group (12.8 ± 6.7 versus 10.1 ± 8.0 IU, p < 0.001 ), no adverse outcomes were observed to be associated with RUPO. Conclusions . The introduction of RUPO significantly reduced blood loss and the incidence of PPH during completed singleton vaginal deliveries without an increase in adverse effects.